1995
DOI: 10.2527/1995.73113253x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of variances due to direct and maternal effects for growth traits of Nelore cattle2

Abstract: Estimates of (co)variance components and genetic parameters were obtained for birth, 205-d, and 365-d weight for Nelore cattle in Brazil, using single and multiple-trait animal models. Data were from the Brazilian Zebu Breeders Association (ABCZ). Records of 27,549 calves sired by 587 bulls and raised on pasture in 57 herds were analyzed by restricted maximum likelihood fitting an animal model including direct and maternal genetic and permanent environmental effects. Single and multiple-trait analyses were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
43
9
43

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 20 publications
17
43
9
43
Order By: Relevance
“…The estimates for weaning weight agreed with values reported for Hereford cattle (Meyer, (Eler et al, 1995), Wakwa and Gudali cattle (Tawah et al, 1993), and Mashona cattle (Khombe et al, 1995). For yearling and final weights, the estimates of direct, but not maternal, heritability were consistent with most published estimates.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The estimates for weaning weight agreed with values reported for Hereford cattle (Meyer, (Eler et al, 1995), Wakwa and Gudali cattle (Tawah et al, 1993), and Mashona cattle (Khombe et al, 1995). For yearling and final weights, the estimates of direct, but not maternal, heritability were consistent with most published estimates.…”
Section: Discussionsupporting
confidence: 80%
“…Maternal effects would be expected to diminish at these ages because the animals no longer depend on their mothers. Relatively high estimates of h 2 were also reported by Eler et al (1995) and Mackinnon et al (1991) at yearling and later ages, respectively. These authors both also suggested that for animals raised on pasture with little or no feed supplement, the length of time between weaning and yearling ages may not be enough to buffer maternal effects present at weaning.…”
Section: Discussionmentioning
confidence: 70%
“…The correlations between direct and maternal genetic effects for all traits were always low and negative (analyses A, C and E). Similar estimates have been reported by Eler et al (1995 and for WW (−0.13) and for BW and WW (−0.33 to −0.14) of Nelore cattle, respectively, and by De Mattos et al (2000) for WW of Hereford cattle in the United States, Canada and Uruguay (−0.51 to −0.31). According to Maniatis and Pollott (2003), the negative estimates obtained for the correlation between direct and maternal genetic effects in the present study might be because of the small number of dams with weight records (18% and 19% for BW and WW, respectively).…”
Section: Resultssupporting
confidence: 86%
“…A seleção com base na avaliação genética de características de desempenho ponderal foi implantada no Brasil de forma até surpreendente (Lôbo et al, 1994;Eler et al, 1995;Fries, 1999) e para características reprodutivas, no entanto, tem sido mais lenta.…”
Section: Introductionunclassified